Playing Roles in Work and Family: Effects of Work/Family Conflicts on Job and Life Satisfaction Among Junior High School Teachers - Li, Xing; Lin, Xinyue; Zhang, Fan; Tian, Yuan (Frontiers in Psychology, 2021)
Junior high school teachers play an essential role in education. How to relieve the worries of teachers, that is, the pressure they face in the fields of work and family, has increasingly become an urgent problem. Based on the COR theory, this study aims to investigate the effects of two types of work/family conflicts (i.e., work-family conflict and family-work conflict) on teachers’ job and life satisfaction. We adopted a handy sample method and collected a total of 560 junior high school teachers' data. The results confirmed that both work-family and family-work conflicts are not significantly related to junior high school teachers’ job satisfaction and life satisfaction directly. However, both work-family and family-work conflicts have significantly negatively influence on junior high school teachers’ job satisfaction and life satisfaction via psychological capital and emotional exhaustion. Our findings provide new suggestions on how to alleviate the conflicts between work and family faced by teachers and further improve their satisfaction about work and family.